2013
DOI: 10.1055/s-0033-1339349
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for the Synthesis of Lipopeptide TLR2-Agonists Using Click Chemistry

Abstract: propyl]cysteine (Pam 2 Cys) is a synthetic lipid motif known to act as a TLR2 agonist when incorporated into peptide vaccines. Herein, we report the synthesis of Pam 2 Cys-containing, propargyl-functionalised 'clickable' building blocks and their conjugation with azide-functionalised antigenic peptides using click chemistry. This method facilitates the fully convergent preparation of self-adjuvanting lipopeptides for use as vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Here, we provide novel synthetic pathways to synthesize N -acetyl Pam 2 Cys analogs with inexpensive materials and avoiding extra orthogonal protection-deprotection steps. Our bioassay results confirmed that the N-acetyl Pam 2 Cys analogs can effectively activate TLR2/6, which is consistent with previous findings that an extra N-acetyl group did not produce any substantial difference in the ability of an Pam 2 CSK 4 analog to induce CD80 expression [18]. Moreover, our docking results suggest that the extra N-acetyl group can be tolerated during ligand-receptor interactions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we provide novel synthetic pathways to synthesize N -acetyl Pam 2 Cys analogs with inexpensive materials and avoiding extra orthogonal protection-deprotection steps. Our bioassay results confirmed that the N-acetyl Pam 2 Cys analogs can effectively activate TLR2/6, which is consistent with previous findings that an extra N-acetyl group did not produce any substantial difference in the ability of an Pam 2 CSK 4 analog to induce CD80 expression [18]. Moreover, our docking results suggest that the extra N-acetyl group can be tolerated during ligand-receptor interactions.…”
Section: Discussionsupporting
confidence: 91%
“…For the receptor-ligand interactions, an X-ray crystal structure of Pam 2 Cys bound to TLR2/TLR6 dimer suggests that the primary amine of the Cys residue does not have a major contribution to the ligand-receptor interactions through any hydrogen bonding interactions [11]. In addition, introducing N-acetylation to Pam 2 Cys analogs was shown to have minimal impact on the compound’s ability to induce immune responses [18].…”
Section: Introductionmentioning
confidence: 99%